PENGARUHNYA RASIO KEUANGAN PADA HARGA SAHAM PERUSAHAAN SUBSEKTOR MINUMAN DAN MAKANAN DI BURSA EFEK INDONESIA MASA 2021-2023 - Ayu Putu Mas Bita Maharani; I Wayan Gde Yogiswara Darma Putra; I Putu Budi Anggririawan (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Warmadewa, 2025)
The food and beverage sector is one of sectors that play an essential contribution to Indonesia's economy as it is related to the essential component of the community. The culinary and beverage industry in Indonesia shows significant development and makes an important contribution to the gross domestic product (GDP). Publicly listed food and beverage companies on the Indonesian stock market generally have strong fundamentals and a good performance record, yet they are prone to experiencing market stock of price fluctuations. The aim of this study is to to empirically analyze the financial ratio value, specifically the debt to equity ratio,net profit margin, return on equity, and earnings per share, in relation to the rapid fluctuations in stock of prices, whether increasing or decreasing, in beverage and food subsector companies are listed on the Indonesia Stock Exchange. The research is conducted using a data of panel analysis regression approach on the annual financial report data of 39 sample companies in beverage and food subsectors listed on the Indonesia Stock Exchange. TheStock price is used as the dependent variable in this research, while the independent variable is the debt-to-equity ratio, return on equity, net profit margin, and earnings per share. The results show that Return on Equity (ROE), Earnings Per Share (EPS), and Debt to Equity Ratio (DER) have an influence on stock prices, while Net Profit Margin (NPM) shows no significant effect on stock prices. This study provides insights for investors in decision making based on financial ratio analysis.